Сучасні особливості економіки та управління персоналом підприємств і організацій - Погорєлова, Тетяна Олексіївна (Національний технічний університет "Харківський політехнічний інститут", 2021)
Метою даної статті є розгляд проблем, з якими стикаються у теперішній час менеджери з персоналу при виконанні своїх функцій для забезпечення ефективної роботи всієї організації. Сучасні умови діяльності підприємств пред'являють якісно нові вимоги до менеджерів з персоналу, обумовлюють необхідність більш високої інтенсивності їхньої праці, уміння цінувати час, володіти комплексом організаційних і психологічних якостей, забезпечувати творчий підхід до роботи. Наголошується, що управління персоналом є стратегічною функцією. Для досягнення поставленої мети розглянуті основні напрями роботи менеджерів з персоналу. Особливу увагу приділено розгляду проблем при відборі та розвитку персоналу. Зроблено висновок, що управління персоналом повинно стати функцією, яка закладена в організаційній стратегії та культурі.

The purpose of this article is to address the challenges that HR managers currently face in performing their functions to ensure the effective operation of the entire organization. Modern conditions of enterprises' activity impose qualitatively new requirements on personnel managers, necessitate a higher intensity of their work, the ability to value time, possess a complex of organizational and psychological qualities, and ensure a creative approach to work. It is noted that personnel management is a strategic function. To achieve this goal, the main directions of work of personnel managers are considered. Particular attention is paid to the consideration of problems in the selection and development of personnel. Human resources departments need to align recruitment and selection processes in line with legal requirements. Career development is one of the keys to attracting and retaining employees. It is noted that there are many factors that will enable an organization to be a better place to work, but the most important of all is organizational culture. It is concluded that Human Resource Management should become a function that is embedded in the organizational strategy and culture.
Modern features of economy and personnel management of enterprises and organizations
Keywords: організація; персонал; планування; розвиток персоналу; управління персоналом; менеджер з персоналу; економіка; підприємство; organization; personnel; personnel development; strategic planning; personnel managementм; personnel manager